Problems of (re-)contextualizing and interpreting variation in oral and written Shaba Swahili - de Rooij, Vincent (Cahiers du Centre de Linguistique et des Sciences du Langage, 2022)
During recent years, many sociolinguists have been arguing that talk, or linguistic form, and socio-cultural and linguistic context are to be seen as mutually constitutive phenomena. Context, then, is no longer regarded as something that is simply given or pre-established of which talk is a mere derivation or reflection. In fact, linguistic interaction is now commonly viewed as a dynamic process in which speakers signal to their interlocutors how to interpret what is being said.